The influence of roads on the fine-scale population genetic structure of the dengue vector Aedes aegypti (Linnaeus). - Maria Angenica F Regilme; Thaddeus M Carvajal; Ann-Christin Honnen; Divina M Amalin; Kozo Watanabe (PLoS Neglected Tropical Diseases, 2021)
Dengue is endemic in tropical and subtropical countries and is transmitted mainly by Aedes aegypti. Mosquito movement can be affected by human-made structures such as roads that can act as a barrier. Roads can influence the population genetic structure of Ae. aegypti. We investigated the genetic structure and gene flow of Ae. aegypti as influenced by a primary road, España Boulevard (EB) with 2000-meter-long stretch and 24-meters-wide in a very fine spatial scale. We hypothesized that Ae. aegypti populations separated by EB will be different due to the limited gene flow as caused by the barrier effect of the road. A total of 359 adults and 17 larvae Ae. aegypti were collected from June to September 2017 in 13 sites across EB. North (N1-N8) and South (S1-S5) comprised of 211 and 165 individuals, respectively. All mosquitoes were genotyped at 11 microsatellite loci. AMOVA FST indicated significant genetic differentiation across the road. The constructed UPGMA dendrogram found 3 genetic groups revealing the clear separation between North and South sites across the road. On the other hand, Bayesian cluster analysis showed four genetic clusters (K = 4) wherein each individual samples have no distinct genetic cluster thus genetic admixture. Our results suggest that human-made landscape features such as primary roads are potential barriers to mosquito movement thereby limiting its gene flow across the road. This information is valuable in designing an effective mosquito control program in a very fine spatial scale.